Off-design comparison of subcritical and partial evaporating ORCs in quasi-steady state annual simulations - Lecompte,S; Chatzopoulou,MA; Markides,C; De,Paepe M (Elsevier, 2019)
The subcritical ORC (SCORC) is considered the industry standard due to its simple configuration, acceptable efficiency and lowcosts. However, it is known that alternative ORC configurations have the potential to increase efficiency. A cycle modification which closely resembles the SCORC is the partial evaporating ORC (PEORC), where a two-phase mixture of liquid-vapour enters the expander instead of superheated vapour. In theoretical studies at design conditions, higher power outputs are achieved for the PEORC compared to the SCORC. This work aims to go a step further by investigating the performance of the SCORC and PEORC under time-dependent operating conditions. A direct comparison between the SCORC and PEORC is made for identically sized systems using as input the waste heat stream of a waste incinerator plant and the changing ambient conditions. Performance maps of both cycle configurations are compiled and the benefit of an expander operating at variable speed is briefly discussed. The results indicate that for the specific case under investigation, the PEORC has an increased annually averaged net power output of 9.6% compared to the SCORC. Use of annually averaged input conditions results in an overestimation of the net power output for both the SCORC and PEORC, and furthermore, the relative improvement in power output for the PEORC is reduced to 6.8%. As such, the use of time-averaged conditions when comparing cycle architectures should preferably be avoided.